Elemental and isotopic composition of heavy noble gases in Allan Hills ice cores - Bender, Michael; Higgins, John; Ng, Jessica; Severinghaus, Jeffrey P.; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2019)
This file includes argon isotope composition and xenon-to-krypton ratios measured in Allan Hills ice cores.